Broiler Production And Economic Well-Being Of Poultry Farmers In Bamenda, Cameroon - Tambi, Mbu Daniel (Convergence: The Journal of Economic Development, 2024)
Abstract Broiler production plays a critical role in enhancing food security and improving economic welfare, particularly in rural areas of developing countries. However, the sector faces several structural challenges that constrain productivity. This study aims to identify and prioritize the key constraints in broiler production and evaluate its impact on farmers’ economic welfare in the Bamenda Municipality. Primary data were collected from broiler farmers and analyzed using the Two-Stage Least Squares (2SLS) estimation technique to address potential endogeneity. The findings reveal that limited access to finance, high input costs, and insufficient knowledge are the most significant constraints, with 90% of respondents citing lack of knowledge as the primary challenge. The regression results indicate that male-headed households, larger household size, farming experience, and participation in solidarity groups are positively and significantly associated with farmers' economic welfare. Access to quality feed is also positively correlated with broiler output. Despite existing challenges, broiler production demonstrates strong economic potential. Based on the findings, it is recommended to adopt low-cost technologies, strengthen extension and veterinary services, and develop market access and input support systems to enhance farmers’ productivity and income. Keywords :  Broiler Production, Economic Welfare, Farming Constraints   Abstrak Produksi broiler berperan penting dalam meningkatkan ketahanan pangan dan kesejahteraan ekonomi, khususnya di daerah pedesaan negara berkembang. Namun, sektor ini menghadapi berbagai kendala struktural yang menghambat produktivitas. Penelitian ini bertujuan mengidentifikasi dan mengurutkan hambatan utama dalam produksi broiler serta menilai dampaknya terhadap kesejahteraan ekonomi peternak di Kotamadya Bamenda. Data primer dikumpulkan dari peternak unggas dan dianalisis menggunakan teknik Two-Stage Least Squares (2SLS) untuk mengatasi endogenitas. Hasil menunjukkan bahwa akses keuangan yang terbatas, tingginya biaya input, dan kurangnya pengetahuan merupakan kendala utama—dengan 90% responden menyebut kurangnya pengetahuan sebagai tantangan terbesar. Model regresi menunjukkan bahwa jenis kelamin kepala rumah tangga (laki-laki), ukuran rumah tangga, pengalaman beternak, dan partisipasi dalam kelompok solidaritas berpengaruh positif signifikan terhadap kesejahteraan ekonomi peternak. Akses terhadap pakan berkualitas juga berdampak positif terhadap produksi broiler. Meskipun banyak tantangan, produksi broiler menunjukkan potensi ekonomi yang besar. Adapun rekomendasi dari hasil penelitian ini yaitu perlu adanya adopsi teknologi murah, peningkatan layanan penyuluhan dan kesehatan hewan, serta pengembangan akses pasar dan dukungan input untuk meningkatkan produktivitas dan pendapatan peternak. Kata kunci : Produksi Ayam Broiler, Kesejahteraan Ekonomi, Tantangan Peternak